Global Development Finance 2004 (Complete Edition) : Harnessing Cyclical Gains for Development - World Bank (Global Development Finance, 2004)
The external financing environment facing developing countries has brightened. In 2003, as global growth gained momentum, private capital flows to developing countries increased to